The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3389/fgene.2021.795201
|View full text |Cite
|
Sign up to set email alerts
|

Combined Metabolome and Transcriptome Analyses of Young, Mature, and Old Rhizome Tissues of Zingiber officinale Roscoe

Abstract: Ginger (Zingiber officinale Roscoe) is known for its unique pungent taste and useability in traditional Chinese medicine. The main compounds in ginger rhizome can be classified as gingerols, diarylheptanoids, and volatile oils. The composition and concentrations of the bioactive compounds in ginger rhizome might vary according to the age of the rhizome. In this regard, the knowledge on the transcriptomic signatures and accumulation of metabolites in young (Y), mature (M), and old (O) ginger rhizomes is scarce.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…This indicates that SAURs may affect cell expansion through the synthesis and transport of auxin under the regulation of ARFs, which are conserved in the plant kingdom [43,45], and function in the regulation of rhizome enlargement in ginger. Liu et al found that the expression of genes related to auxin signaling pathway was higher in young ginger tissues and lower in mature and old tissues [46]. The reason for the inconsistent results may be that the rhizome enlargement period we studied was before the maturity period of Liu et al No more auxin is required after the completion of the expansion process, so auxin-related gene expression is reduced in mature and old tissues.…”
Section: Other Hormone Changes In Ginger Rhizome Enlargementmentioning
confidence: 80%
See 1 more Smart Citation
“…This indicates that SAURs may affect cell expansion through the synthesis and transport of auxin under the regulation of ARFs, which are conserved in the plant kingdom [43,45], and function in the regulation of rhizome enlargement in ginger. Liu et al found that the expression of genes related to auxin signaling pathway was higher in young ginger tissues and lower in mature and old tissues [46]. The reason for the inconsistent results may be that the rhizome enlargement period we studied was before the maturity period of Liu et al No more auxin is required after the completion of the expansion process, so auxin-related gene expression is reduced in mature and old tissues.…”
Section: Other Hormone Changes In Ginger Rhizome Enlargementmentioning
confidence: 80%
“…However, BRs have been shown to play an important role in controlling cell elongation and can induce the expression of SAUR genes [52,53]. In Liu et al's study, most DEGs enriched in plant hormone signals such as ethylene, BRs, JA and SAwere relatively highly expressed in young ginger rhizomes, and played important roles in ginger rhizome growth [46]. In our study, the JA content increased with the development of ginger, which is consistent with the upregulation of all three JA biosynthesis-related JA O-methyltransferase and JAR genes through the S1-S2 and S2-S3 transitions (Fig 1C and S5 Table).…”
Section: Other Hormone Changes In Ginger Rhizome Enlargementmentioning
confidence: 95%
“…Herein, the aqueous extract of Z. officinale rhizome was used for the green synthesis of AuNPs. As reported previously, Z. officinale rhizome provides an enriched source for various constituents, such as terpenes, lipids, phenolic compounds, polysaccharides, organic acids, and volatile oils [49,50]. These metabolites were used as biocatalyst to reduce metals and their oxide to produce nanoscale structures, followed by capping and stabilization (mediated by the extracted compounds).…”
Section: Green Synthesis Of Aunpsmentioning
confidence: 93%
“…Samples were prepared following the protocol described by Liu et al. (2021). Briefly, the samples were ground into a powder and subjected to lyophilization under vacuum.…”
Section: Methodsmentioning
confidence: 99%